Iklan Pariwara Galaxy S8 di Media Berita Online - Muhammad Zulvikar Pahlevi Nurlette; Muhammad Edy Susilo; Christina Rochayanti (Jurnal Paradigma, 2018)
Manufactures continue to do new things in marketing communication